Anti-counterfeiting material as well as preparation method and application thereof

By fluorinating the fibers and nano-coating, combined with the pulp preparation process, anti-counterfeiting materials with different friction coefficients, textures and mechanical properties are prepared, which solves the problem that traditional anti-counterfeiting methods are easily imitated and realizes the physical and tactile properties based on efficient anti-counterfeiting effect.

CN119392530APending Publication Date: 2025-02-07SHENZHEN GLAREWAY TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411550501.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Traditional anti-counterfeiting methods such as watermarks, fluorescent inks or holograms have gradually shown the possibility of being copied, and their anti-counterfeiting functions are challenged and there is a problem of being easily imitated.

Method used

Tactile reinforcement fibers are obtained by soaking the base fibers in fluorinating agent or mixing them with nanoparticles, and pulping is mixed with other fibers, fillers and solvents, and shaped by pulp spreading, water removal, forming, pressing and drying. , prepare anti-counterfeiting materials with different areas of surface friction coefficient, texture and mechanical properties.

Benefits of technology

The anti-counterfeiting effect through physical and tactile attributes is achieved, so that different areas of the paper surface have significant tactile differences and are difficult to imitate. It is suitable for packaging and printing paper in the field of anti-counterfeiting.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392530A_ABST
    Figure CN119392530A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of anti-counterfeiting materials, and particularly relates to an anti-counterfeiting material and a preparation method and application thereof. According to the anti-counterfeiting material provided by the invention, through a special fiber material and a surface treatment technology, the surface friction coefficient, the texture structure and the mechanical property of the fiber material are controlled, so that different areas of the surface of paper have different hand feelings and have obvious differences in touch sense, and the paper is difficult to imitate. The invention also provides application of the anti-counterfeiting material in the anti-counterfeiting field or the anti-counterfeiting material obtained by the preparation method in the anti-counterfeiting field. The anti-counterfeiting material provided by the invention is anti-counterfeiting based on physical and tactile attributes, is difficult to imitate, and can be used in the anti-counterfeiting field, such as packaging, especially packaging printing paper anti-counterfeiting.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of anti-counterfeiting materials, and in particular relates to an anti-counterfeiting material and a preparation method and application thereof. Background Art

[0002] In order to verify the authenticity of some valuable items, people generally use various anti-counterfeiting technologies, especially in the fields of currency, certificates, bills, pharmaceutical packaging and luxury goods, such as special marking.

[0003] In order to improve the level of anti-counterfeiting, governments and enterprises have invested a lot of money to develop a variety of anti-counterfeiting technologies. Traditional anti-counterfeiting methods, such as watermarks, fluorescent inks or holograms, have been used for many years. With the improvement of counterfeiting technology, these methods have gradually shown the possibility of being copied, and their anti-counterfeiting functions have been challenged and there is a problem of being easily imitated. Summary of the invention

[0004] The purpose of the present invention is to provide an anti-counterfeiting material and a preparation method and application thereof. The anti-counterfeiting material provided by the present invention is anti-counterfeiting based on physical and tactile properties and is difficult to imitate.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing an anti-counterfeiting material, comprising the following steps:

[0007] The base fiber A is soaked in a fluorinating agent and then taken out and dried, or the base fiber A is mixed with nanoparticles for nano-coating to obtain a fiber with enhanced touch;

[0008] The touch-enhancing fiber is mixed with the base fiber B, the functional fiber, the filler and the solvent to make pulp, and then the pulp is spread, dehydrated, formed, pressed and dried to obtain the anti-counterfeiting material.

[0009] Preferably, the base fiber A is cotton fiber.

[0010] Preferably, the nanoparticles include one or both of titanium dioxide nanoparticles and silicon oxide nanoparticles.

[0011] Preferably, the nano-coating is electrostatic adsorption or chemical bonding; the electrostatic adsorption is: immersing the base fiber A in a nanoparticle suspension and then drying and low-temperature plasma treatment in sequence; the chemical bonding is: mixing the base fiber A, a silane coupling agent and a nanoparticle suspension, and performing a substitution reaction while stirring.

[0012] Preferably, the functional fiber is polyester fiber.

[0013] Preferably, the mass ratio of the basic fiber B to the functional fiber is 40-60:20-30; the mass ratio of the basic fiber B to the touch-enhancing fiber is 40-60:10-20; the mass ratio of the basic fiber B to the filler is 40-60:5-10.

[0014] Preferably, the pressing is: under heating conditions, pressurizing the surface of the paper and then pressing the texture; the heating temperature is 80-150°C; the pressurizing is gradual; the gradual pressurizing is: starting from 0.1-0.3MPa and then gradually increasing the pressure to 0.5-1.0MPa.

[0015] Preferably, the drying and shaping is carried out in sequence by low-temperature drying and high-temperature drying; the temperature of the low-temperature drying is 60-90°C, and the target moisture content is 30-40wt%; the temperature of the high-temperature drying is 90-150°C, and the target moisture content is 5-8wt%.

[0016] The present invention also provides an anti-counterfeiting material obtained by the preparation method described in the above scheme, wherein the friction coefficient, texture and mechanical properties of different areas on the surface of the anti-counterfeiting material are different.

[0017] The present invention also provides the application of the anti-counterfeiting material described in the above scheme in the field of anti-counterfeiting.

[0018] The present invention provides an anti-counterfeiting material. The anti-counterfeiting material provided by the present invention controls the surface friction coefficient (0.2-0.4), texture structure and mechanical properties of the fiber material through special fiber materials and surface treatment technology, so that different areas on the surface of the paper have different hand feelings and significant differences in touch, making it difficult to imitate.

[0019] The present invention also provides a method for preparing the anti-counterfeiting material of the above scheme. The preparation method provided by the present invention has simple steps, convenient operation, good feasibility and low cost.

[0020] The present invention also provides the application of the anti-counterfeiting material in the anti-counterfeiting field. The anti-counterfeiting material provided by the present invention is anti-counterfeiting based on physical and tactile properties and is difficult to imitate, and can be used in the anti-counterfeiting field, such as packaging, especially packaging printing paper anti-counterfeiting. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1The present invention is a process flow chart for preparing anti-counterfeiting materials. DETAILED DESCRIPTION

[0023] The present invention provides a method for preparing an anti-counterfeiting material, comprising the following steps:

[0024] The base fiber A is soaked in a fluorinating agent and then taken out and dried, or the base fiber A is mixed with nanoparticles for nano-coating to obtain a fiber with enhanced touch;

[0025] The touch-enhancing fiber is mixed with the base fiber B, the functional fiber, the filler and the solvent to make pulp, and then the pulp is spread, dehydrated, formed, pressed and dried to obtain the anti-counterfeiting material.

[0026] In the present invention, the base fiber A is soaked in a fluorinating agent (referred to as the first soaking) and then taken out and dried (referred to as the first drying) to obtain a fiber with enhanced touch. In the present invention, the base fiber A is preferably cotton fiber. In the present invention, cotton fiber with a soft and natural touch is used as the base fiber A.

[0027] In the present invention, the base fiber A is preferably washed before use; the washing is preferably performed in sequence of water washing and alcohol washing; the alcohol used in the alcohol washing is preferably ethanol. The present invention removes impurities on the surface of the base fiber A by washing.

[0028] In the present invention, the fluorinating agent preferably includes fluorosilane (C6H 13 FO2Si) and perfluoroalkyl polyurethane; the fluorinating agent is preferably used in the form of a fluorinating agent solution; the solvent of the fluorinating agent solution is preferably an organic solvent; the organic solvent is preferably isopropanol; the concentration of the fluorinating agent solution is preferably 0.5-1wt%, specifically 0.5wt%, 0.7wt%, 0.9wt% or 1wt%. The present invention is chemically modified by fluorination treatment to reduce the surface friction coefficient of the base fiber A, give the fiber a smooth touch, and form a hydrophobic surface.

[0029] In the present invention, the first immersion time is preferably 10 to 30 minutes, and specifically preferably 10 minutes, 15 minutes, 20 minutes, 25 minutes or 30 minutes.

[0030] In the present invention, the first drying is preferably drying; the drying temperature is preferably 80-100°C, specifically 80°C, 85°C, 90°C, 95°C or 100°C, and the heat preservation and drying time is preferably 1-2 hours, specifically 1.5 hours. The present invention ensures that the fluoride is stably attached to the fiber surface through the first drying.

[0031] Alternatively, the present invention mixes the base fiber A and nanoparticles for nano-coating to obtain a touch-enhanced fiber. In the present invention, the nanoparticles preferably include one or both of titanium dioxide (TiO2) nanoparticles and silicon oxide (SiO2) nanoparticles.

[0032] In the present invention, the nano coating is preferably electrostatic adsorption or chemical bonding. In the present invention, nanoparticles are uniformly attached to the fiber surface by electrostatic adsorption or chemical bonding to form a nanoscale surface structure - nanoparticle coating. The nanoparticle coating can enhance the wear resistance and special touch of the fiber. Different particle materials can bring different touches, such as smooth, rough or delicate.

[0033] In the present invention, the electrostatic adsorption is preferably: soaking the base fiber A in the nanoparticle suspension (referred to as the second soaking) and then drying (referred to as the second drying) and low-temperature plasma treatment in sequence.

[0034] In the present invention, the solvent of the nanoparticle suspension is preferably alcohol; the alcohol is preferably ethanol; the concentration of the nanoparticle suspension is preferably 0.1-0.5wt%, specifically 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt% or 0.5wt%. The present invention uses ethanol, which is relatively non-toxic and has a fast drying speed.

[0035] In the present invention, the second immersion time is preferably 5 to 15 minutes, specifically 5 minutes, 7 minutes, 10 minutes, 12 minutes or 15 minutes.

[0036] In the present invention, the second drying is preferably oven drying; the drying temperature is preferably 60-80°C, specifically 60°C, 65°C, 70°C, 75°C or 80°C, and the heat preservation and drying time is preferably based on uniform attachment of the nanoparticles.

[0037] In the present invention, the low-temperature plasma treatment is preferably performed by placing the dried fiber in a vacuum chamber, introducing oxygen after evacuation, and turning on a radio frequency power supply to perform plasma treatment.

[0038] In the present invention, the vacuum pump is preferably a vacuum pump; the target vacuum degree of the vacuum pump is preferably 1Pa; the oxygen-introducing device is preferably a plasma generator; the gas flow rate of the oxygen-introducing device is preferably 50mL / min; the power of the low-temperature plasma treatment is preferably 100W, and the treatment time is preferably 30 seconds. Low-temperature plasma treatment generates high-energy electrons and ions in a low-pressure environment, and these high-energy particles react with the surface of the material, thereby changing the chemical composition and physical structure of the surface. The present invention increases the bonding strength between the nanoparticles and the base fiber A through low-temperature plasma treatment.

[0039] In the present invention, the chemical bonding is preferably carried out by mixing the base fiber A, the silane coupling agent and the nanoparticle suspension, and performing an etherification reaction while stirring.

[0040] In the present invention, the nanoparticles in the nanoparticle suspension preferably include one or both of titanium dioxide (TiO2) nanoparticles and silicon oxide (SiO2) nanoparticles; the solvent of the nanoparticle suspension is preferably alcohol; and the alcohol is preferably ethanol.

[0041] In the present invention, the concentration of the nanoparticle suspension is preferably 0.1-0.5 wt%, specifically 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt% or 0.5 wt%.

[0042] In the present invention, the silane coupling agent preferably includes one or both of γ-aminopropyltriethoxysilane (APTES) and γ-glycidoxypropyltrimethoxysilane (GPTMS); the mass ratio of the silane coupling agent to the nanoparticle suspension is preferably 0.1-0.3:100, specifically 0.2:100.

[0043] In the present invention, the temperature of the etherification reaction is preferably 60-80°C, specifically 60°C, 65°C, 70°C, 75°C or 80°C, and the heat preservation reaction time is preferably 3-5 hours, specifically 3 hours, 3.5 hours, 4 hours, 4.5 hours and 5 hours. The present invention allows the silane coupling agent to react with the hydroxyl groups on the surface of the nanoparticles and react with the base fiber A through the etherification reaction, and the reaction process is as follows:

[0044] NH2-(CH2)3-Si-(OH)3+3HO-Surface→NH2-(CH2)3-Si-O-Surface+3H2O.

[0045] In the present invention, after the etherification reaction, the reaction product is preferably washed and then dried; the washing is preferably alcohol washing; the alcohol used in the alcohol washing is preferably ethanol. The present invention removes the unreacted silane coupling agent by washing.

[0046] After obtaining the touch-enhancing fiber, the present invention mixes the touch-enhancing fiber with the base fiber B, the functional fiber, the filler and the solvent to obtain pulp. In the present invention, the length of the touch-enhancing fiber is preferably 3 to 5 mm, specifically 3 mm, 3.5 mm, 4 mm, 4.5 mm or 5 mm.

[0047] In the present invention, the functional fiber is preferably polyester fiber; the length of the functional fiber is preferably 3 to 5 mm, specifically 3 mm, 3.5 mm, 4 mm, 4.5 mm or 5 mm.

[0048] In the present invention, the base fiber B is preferably cotton fiber.

[0049] In the present invention, the length of the basic fiber B is preferably 1 to 3 mm, specifically 2 mm. The present invention controls the length of the basic fiber B within the above range, which can avoid the uneven pulp caused by excessively long fibers and the influence of excessively short fibers on the strength of the paper.

[0050] In the present invention, the base fiber B is preferably pretreated before use; the pretreatment is preferably: cutting and bleaching the base fiber B raw material in sequence. The present invention cuts the base fiber B to have a suitable size and properties, ensures that the fiber is suitable for mixing and pulping, makes the fiber evenly dispersed in the pulp, and improves the uniformity of the paper; and bleaching, the bleaching agent reacts with the lignin in the base fiber B, removes the color, and enhances the brightness and cleanliness of the fiber.

[0051] In the present invention, the bleaching is preferably performed by: soaking the cut base fiber B in a bleaching solution and then washing; the bleaching solution preferably includes a bleaching agent and water; the bleaching agent preferably includes sodium chlorate (NaClO3) or hydrogen peroxide (H2O2); the concentration of the bleaching solution is preferably 2 to 5wt%, specifically 2wt%, 3wt%, 4wt% or 5wt%.

[0052] In the present invention, the bleaching temperature is preferably 50-60°C, specifically 55°C, the time is preferably 30-60 minutes, specifically 40 minutes or 50 minutes; the washing is preferably water washing. The present invention removes excess bleaching agent by washing.

[0053] In the present invention, the mass ratio of the base fiber B to the functional fiber is preferably 40-60:20-30, specifically 40:20, 50:20, 60:20, 40:25, 60:25, 40:30 or 50:30.

[0054] In the present invention, the mass ratio of the base fiber B to the touch enhancing fiber is preferably 40-60:10-20, and specifically may be 40:10, 50:10, 60:10, 40:15, 50:15, 40:20, 50:20 or 60:20.

[0055] In the present invention, the filler preferably includes one or both of calcium carbonate and titanium dioxide. The present invention can increase the thickness and opacity of paper by adding fillers.

[0056] In the present invention, the mass ratio of the base fiber B to the filler is preferably 40-60:5-10, specifically 40:5, 50:5, 60:5, 40:7, 50:7, 60:7, 40:9, 50:9, 60:9, 40:10, 50:10 or 60:10.

[0057] The present invention uses the basic fiber B to provide the basic strength and toughness of the paper, uses the functional fiber to provide specific functions, such as tear resistance, hydrophobicity or enhanced touch, uses the touch-enhancing fiber to give the paper a unique touch, and uses the filler to increase the opacity and thickness of the paper.

[0058] In the present invention, the solvent is preferably water.

[0059] In the present invention, the concentration of the basic fiber B in the pulp is preferably 3-5wt%, specifically 3wt%, 3.5wt%, 4wt%, 4.5wt% or 5wt%.

[0060] In the present invention, the pulping is preferably: mixing base fiber and water (referred to as mixing A) to obtain mixture A, mixing mixture A and functional fiber (referred to as mixing B) to obtain mixture B, and mixing mixture B and filler (referred to as mixing C).

[0061] In the present invention, the mixing A is preferably stirring mixing, the stirring mixing speed is preferably 500-1000rpm, specifically 500rpm, 700rpm or 1000rpm, the mixing temperature is preferably 40-50°C, specifically 45°C, and the mixing time is preferably 20-30 minutes, specifically 15 minutes.

[0062] In the present invention, the mixing B is preferably stirred and mixed, the stirring and mixing speed is preferably 500-1000 rpm, specifically 500 rpm, 700 rpm or 1000 rpm, the mixing temperature is preferably 40-50° C., specifically 45° C., and the mixing time is preferably 10-15 minutes, specifically 12 minutes. The present invention disperses the components uniformly by mixing B.

[0063] In the present invention, the mixing C is preferably stirring mixing, the stirring mixing speed is preferably 500-1000rpm, specifically 500rpm, 700rpm or 1000rpm, the mixing temperature is preferably 40-50°C, specifically 45°C, and the mixing time is preferably 10-15 minutes, specifically 10 minutes.

[0064] The present invention prevents fiber agglomeration by controlling the mixing speed and helps maintain the fluidity of the pulp by controlling the mixing temperature, thereby achieving control of the uniformity of the pulp and the fiber distribution.

[0065] After obtaining the pulp, the present invention sequentially performs pulp spreading, dehydration, forming, pressing and drying to obtain the anti-counterfeiting material. In the present invention, the pulp spreading is preferably: the pulp is transported to the moving forming mesh of the cylinder paper machine for spreading. The forming section in the cylinder paper machine is responsible for evenly spreading the pulp to ensure that the fibers of each part of the paper are evenly distributed.

[0066] In the present invention, the spreading amount of the pulp is preferably 230 to 235 g / m 2 , specifically 232g / m 2 The present invention controls the spreading thickness of the paper by adjusting the opening size of the headbox and the pulp flow rate.

[0067] In the present invention, the moving speed of the forming mesh is preferably 20-30 m / min, specifically 25 m / min. The present invention adjusts the moving speed of the forming mesh according to the thickness of the paper.

[0068] In the present invention, the dehydration preferably includes gravity dehydration and suction roller dehydration; the target water content of the dehydration is preferably 50-60wt%. The forming mesh gradually removes water by gravity and suction roller, and the pulp begins to be initially formed.

[0069] In the present invention, the forming preferably includes dehydration and initial pressing in sequence; the target moisture content of the dehydration is preferably 40-50wt%; the dehydration equipment is preferably a vacuum suction roller; the initial pressing pressure is preferably 0.05-0.1MPa, specifically 0.05MPa, 0.07MPa, 0.09MPa or 0.1MPa, and the initial pressing time is preferably adjusted by the speed of the forming mesh; the speed of the forming mesh is preferably 20-30m / min, specifically 25m / min.

[0070] After the pulp is evenly spread, the forming mesh continues to move forward, and the paper is gradually dehydrated and solidified. At this time, the initial thickness and fiber arrangement of the paper have been roughly determined, but it still contains a large amount of water. The present invention increases the strength of the paper by dehydration, prevents damage in subsequent processes, and ensures the finalization of the paper structure by initial pressing.

[0071] In the present invention, the pressing is preferably performed by applying pressure to the surface of the paper under heating conditions and then pressing the texture.

[0072] In the present invention, the heating temperature is preferably 80-150°C; the heating device is preferably a heating roller. The present invention heats the paper during the pressing process, and the heating temperature is adjusted according to the type of paper, so that the paper is further shaped and cured under the action of pressure and temperature, which can not only enhance the mechanical properties of the paper, but also fix the surface structure of the touch-enhancing fibers to prevent the touch-enhancing fibers from loosening.

[0073] In the present invention, the pressurizing device is preferably a high-pressure roller or a multi-roller press; the pressurizing time is preferably adjusted by the speed of the pressurizing roller; the speed of the pressurizing roller is preferably 50-60 m / min, specifically 55 m / min; the pressurizing target thickness is preferably 0.1-0.2 mm, specifically 0.15 mm. The present invention adjusts the thickness of the paper by pressurizing.

[0074] In the present invention, the pressurization is preferably gradual pressurization; the gradual pressurization is preferably: starting from 0.1-0.3 MPa, and then gradually increasing the pressure to 0.5-1.0 MPa; the rate of pressurization is preferably 0.1 MPa / min. The present invention applies different degrees of pressure to the paper to achieve the desired thickness and surface flatness.

[0075] In the present invention, the texture pressing device is preferably a pattern pressing roller; the target texture of the texture pressing is preferably to produce a difference in touch, specifically a combination of fine and rough hand feeling or a combination of corrugated and patterned effects; the pattern depth of the pattern pressing roller is preferably 50-100 μm, specifically 70 μm or 90 μm. The present invention controls the surface texture of the paper, presses a specific pattern or texture on the surface of the paper, and uses different roller surface treatments to give different areas of the paper different touch feelings, such as fine, rough or corrugated. The depth and shape of the pattern are determined by the design of the pattern pressing roller.

[0076] In the present invention, the drying and shaping is preferably carried out in sequence by low-temperature drying and high-temperature drying; the temperature of the low-temperature drying is preferably 60-90°C, specifically 70°C or 80°C, and the target moisture content is preferably 30-40wt%.

[0077] In the present invention, the temperature of the high temperature drying is preferably 90-150° C., specifically 110° C. or 130° C., and the target moisture content is preferably 5-8 wt %. The main process of preparing the anti-counterfeiting material of the present invention is as follows: Figure 1 shown.

[0078] The present invention also provides an anti-counterfeiting material obtained by the preparation method described in the above scheme, wherein the friction coefficient, texture and mechanical properties of different areas on the surface of the anti-counterfeiting material are different.

[0079] The present invention adopts the preparation method described in the above scheme, and obtains anti-counterfeiting materials with different textures by adjusting parameters, and can be produced according to customer needs. For example, some packaging requires a higher friction coefficient to ensure stable transmission and stacking of the packaging on the production line; some packaging requires a lower friction coefficient to facilitate the molding of the packaging machine.

[0080] In the present invention, the thickness of the anti-counterfeiting material is preferably 0.18-0.30 mm, specifically 0.18 mm, 0.20 mm, 0.24 mm, 0.27 mm or 0.30 mm.

[0081] The present invention also provides the application of the anti-counterfeiting material described in the above scheme in the field of anti-counterfeiting.

[0082] The anti-counterfeiting material provided by the present invention is anti-counterfeiting based on physical and tactile properties and is difficult to imitate. It can be used in the field of anti-counterfeiting, such as packaging, and can be used as packaging printing paper for anti-counterfeiting. It is particularly suitable for packaging high-end gifts and making handmade boxes. It can enhance the appearance, texture and touch of the product and has an anti-counterfeiting effect.

[0083] In order to further illustrate the present invention, the scheme of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be understood as limiting the protection scope of the present invention.

[0084] Example 1

[0085] The method for preparing the anti-counterfeiting material in this embodiment includes the following steps:

[0086] (1) The cotton fiber was washed with water and ethanol in sequence, then immersed in a fluorosilane solution (concentration of 0.8 wt%) for 25 minutes, taken out, and dried at 100° C. for 2 hours to obtain a touch-enhancing fiber (length of 5 mm).

[0087] (2) The cotton fiber raw material was cut, and the cut cotton fiber was immersed in a bleaching solution (sodium chlorate aqueous solution, concentration of 4 wt%) at 60° C. for 60 minutes, and then washed to obtain cotton fiber with a length of 3 mm.

[0088] (3) At 50° C. and 850 rpm, cotton fiber and water were stirred and mixed for 30 minutes to obtain a mixture A, mixture A and polyester fiber (length 5 mm) were mixed for 15 minutes to obtain a mixture B, mixture B and calcium carbonate were mixed for 15 minutes to prepare pulp to obtain a pulp, wherein the concentration of cotton fiber in the pulp was 5 wt %, the mass ratio of cotton fiber to polyester fiber was 50:20, the mass ratio of cotton fiber to touch enhancing fiber was 50:20, and the mass ratio of cotton fiber to calcium carbonate was 50:10.

[0089] (4) The pulp is transported to the moving forming mesh of the cylinder paper machine (moving speed is 25m / min) and spread, with a spreading amount of 230g / m 2After the pulp is evenly spread, the forming mesh continues to move forward, and the pulp is dehydrated by gravity, dehydrated by the suction roller (to a moisture content of 58wt%), dehydrated (to a moisture content of 40wt%) and initially pressed (pressure of 0.06MPa). Under heating conditions of 120°C, pressure is applied at 0.1MPa on the surface of the paper, and then gradually increased to 1.0MPa. The texture is then pressed with a pattern pressing roller (the pattern depth is 50μm), dried at 80°C to a moisture content of 35wt%, and dried at 120°C to a moisture content of 8wt%, to obtain an anti-counterfeiting material.

[0090] Example 2

[0091] The method for preparing the anti-counterfeiting material in this embodiment includes the following steps:

[0092] (1) Cotton fibers were immersed in a suspension of γ-aminopropyltriethoxysilane and titanium dioxide nanoparticles (concentration of 0.4 wt%), with a mass ratio of silane coupling agent to nanoparticle suspension of 0.2:100, and etherification reaction was carried out at 70° C. for 4 hours while stirring, and then washed with alcohol and dried to obtain touch-enhanced fibers (length of 3 mm).

[0093] (2) The cotton fiber raw material is cut, and the cut cotton fiber is immersed in a bleaching solution (sodium chlorate aqueous solution, concentration is 4wt%) at 50-60°C for 60 minutes, and then washed to obtain cotton fiber with a length of 3 mm.

[0094] (3) At 50° C. and 900 rpm, cotton fiber and water were stirred to obtain mixture A, mixture A and polyester fiber (length 3 mm) were mixed for 13 minutes to obtain mixture B, mixture B and calcium carbonate were mixed for 13 minutes to prepare pulp, and the concentration of cotton fiber in the pulp was 5 wt %, the mass ratio of cotton fiber to polyester fiber was 60:20, the mass ratio of cotton fiber to touch enhancing fiber was 60:20, and the mass ratio of cotton fiber to calcium carbonate was 60:10.

[0095] (4) The pulp is transported to the moving forming mesh of the cylinder paper machine (moving speed is 25m / min) and spread, with a spreading amount of 230g / m 2 After the pulp is evenly spread, the forming mesh continues to move forward, and the pulp is dehydrated by gravity, dehydrated by the suction roller (to a moisture content of 55wt%), dehydrated (to a moisture content of 38wt%) and initially pressed (pressure of 0.07MPa). Under heating conditions of 130°C, pressure is applied at 0.1MPa on the surface of the paper, and then gradually increased to 1MPa. The texture is then pressed with a pattern pressing roller (the pattern depth is 65μm), dried at 80°C to a moisture content of 30wt%, and dried at 150°C to a moisture content of 7wt%, to obtain an anti-counterfeiting material.

[0096] Example 3

[0097] The method for preparing the anti-counterfeiting material in this embodiment includes the following steps:

[0098] (1) Cotton fibers were immersed in a titanium dioxide nanoparticle suspension (concentration of 0.5 wt%) for 15 minutes, dried at 80° C., and treated with low-temperature plasma to obtain touch-enhanced fibers (length of 3 mm).

[0099] (2) The cotton fiber raw material is cut, and the cut cotton fiber is immersed in a bleaching solution (sodium chlorate aqueous solution, concentration is 3wt%) at 60°C for 30 to 60 minutes, and then washed to obtain cotton fiber with a length of 3 mm.

[0100] (3) At 50° C. and 800 rpm, cotton fiber and water were stirred to obtain a mixture A, mixture A and polyester fiber (length 5 mm) were mixed for 15 minutes to obtain a mixture B, mixture B and calcium carbonate were mixed for 15 minutes to prepare pulp to obtain a pulp, wherein the concentration of cotton fiber in the pulp was 4 wt %, the mass ratio of cotton fiber to polyester fiber was 52:23, the mass ratio of cotton fiber to touch enhancing fiber was 52:17, and the mass ratio of cotton fiber to calcium carbonate was 52:7.

[0101] (4) The pulp is transported to the moving forming mesh of the cylinder paper machine (moving speed is 22m / min) and spread, with a spreading amount of 230g / m 2 After the pulp is evenly spread, the forming mesh continues to move forward, and the pulp is dehydrated by gravity, dehydrated by the suction roller (to a moisture content of 52wt%), dehydrated (to a moisture content of 36wt%), and initially pressed (pressure of 0.06MPa). Under heating conditions of 130°C, pressure is applied on the surface of the paper at 0.1MPa, and then gradually increased to 0.7MPa. The texture is then pressed with a pattern pressing roller (the pattern depth is 50μm), dried at 90°C to a moisture content of 37wt%, and dried at 150°C to a moisture content of 7wt%, to obtain an anti-counterfeiting material.

[0102] Test Example 1

[0103] The treatment effect of the touch-enhancing fiber prepared in Example 1 was tested:

[0104] (1) Surface friction coefficient test: Use a friction coefficient meter to measure the friction coefficient between the treated fiber and the standard surface, record the friction coefficient value, and determine the tactile enhancement effect.

[0105] Standard: By testing the friction coefficient between the fiber and the standard surface, the value is controlled between 0.2 and 0.4, and is adjusted according to the specific requirements of the paper.

[0106] (2) Contact angle test: Use a contact angle meter to measure the contact angle of the treated fiber and record it to ensure that the chemical treatment is effective.

[0107] Standard: The contact angle of the treated fiber should be greater than 90° (hydrophobic treatment).

[0108] (3) Electron microscopy (SEM): The surface structure of the treated fibers was observed using a scanning electron microscope (SEM) to observe and record the particle distribution.

[0109] Criteria: Ensure that the nano-coating or chemical modification is evenly distributed and that particles are evenly attached without excessive agglomeration.

[0110] (4) Tensile strength test: Use a tensile testing machine to test the strength of the treated fiber and record it.

[0111] Standard: Ensure that the fiber does not lose too much mechanical properties due to treatment. The tensile strength of the treated fiber should be maintained at more than 90% of the original strength. The specific test results are shown in Table 1.

[0112] Table 1 Test results of the touch-enhancing fibers of Example 1

[0113] Test items Measured data 1 0.32 2 105° 3 Even distribution 4 92%

[0114] It can be seen from Table 1 that the touch-enhancing fiber prepared in this example meets the requirements of various indicators.

[0115] Test Example 2

[0116] The anti-counterfeiting material prepared in Example 1 was tested:

[0117] (1) Thickness measurement: Use a micrometer or paper thickness tester to measure the paper thickness, record the thickness values ​​at multiple points and calculate the average value.

[0118] Standard: Paper thickness should be controlled within 0.1-0.2mm, and the thickness error should be less than ±0.01mm.

[0119] (2) Surface flatness detection: Use an optical surface analyzer to measure the surface flatness of the paper and record the flatness data.

[0120] Standard: The flatness error should be less than 5μm, ensuring that the paper surface is smooth without obvious bumps.

[0121] (3) Surface texture detection: Use a scanning electron microscope or a 3D surface profiler to observe the surface texture of the paper and measure the depth and uniformity of the pressed texture.

[0122] Standard: Texture depth should be controlled within 50-200μm, and texture uniformity error should be less than ±10μm.

[0123] (4) Moisture content detection: Use a moisture analyzer to measure the residual moisture in the paper and record the moisture content percentage.

[0124] Standard: The moisture content of paper should be controlled between 5% and 8%. Too high a moisture content will cause the paper to deform or affect the anti-counterfeiting effect.

[0125] (5) Tear strength test: Use a tear strength tester to measure the tear resistance of paper and record the tear strength value.

[0126] Standard: The tear strength of paper should reach 1~3N, which should be adjusted according to the application requirements of paper.

[0127] The quality test data obtained are shown in Table 2.

[0128] Table 2 Test results of anti-counterfeiting materials of Example 1

[0129] Test items Measured data 1 0.15mm 2 3μm 3 120μm, ±8μm 4 6.5% 5 2.3N

[0130] It can be seen from Table 2 that the anti-counterfeiting material prepared in this embodiment meets the requirements of various indicators, has a smooth surface, uniform texture in each area, and excellent tear resistance.

[0131] It can be seen from the above embodiments that the anti-counterfeiting material provided by the present invention is based on physical and tactile properties for anti-counterfeiting, has a unique appearance and special touch, is difficult to imitate, and can be used in the field of anti-counterfeiting.

[0132] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing an anti-counterfeiting material, characterized in that: The following steps are involved: The base fiber A is soaked in a fluorinating agent and then taken out and dried, or the base fiber A is mixed with nanoparticles for nano-coating to obtain a fiber with enhanced touch; The touch-enhancing fiber is mixed with the base fiber B, the functional fiber, the filler and the solvent to make pulp, and then the pulp is spread, dehydrated, formed, pressed and dried to obtain the anti-counterfeiting material.

2. The preparation method according to claim 1, characterized in that: The base fiber A is cotton fiber.

3. The preparation method according to claim 1 or 2, characterized in that: The nanoparticles include one or both of titanium dioxide nanoparticles and silicon oxide nanoparticles.

4. The preparation method according to claim 1, characterized in that: The nano-coating is electrostatic adsorption or chemical bonding; the electrostatic adsorption is: soaking the base fiber A in a nanoparticle suspension and then drying and low-temperature plasma treatment in sequence; the chemical bonding is: mixing the base fiber A, a silane coupling agent and a nanoparticle suspension, and performing a substitution reaction while stirring.

5. The preparation method according to claim 1, characterized in that: The functional fiber is polyester fiber.

6. The preparation method according to claim 1 or 5, characterized in that: The mass ratio of the basic fiber B to the functional fiber is 40-60:20-30; the mass ratio of the basic fiber B to the touch-enhancing fiber is 40-60:10-20; the mass ratio of the basic fiber B to the filler is 40-60:5-10.

7. The preparation method according to claim 1, characterized in that: The pressing comprises: applying pressure on the surface of the paper under heating conditions, and then pressing the texture; the heating temperature is 80-150° C.; the pressing is performed step by step; the stepwise pressing comprises: starting from 0.1-0.3 MPa, and then gradually increasing the pressure to 0.5-1.0 MPa.

8. The preparation method according to claim 1 or 7, characterized in that: The drying and shaping is carried out in sequence by low-temperature drying and high-temperature drying; the temperature of the low-temperature drying is 60-90° C., and the target moisture content is 30-40wt%; the temperature of the high-temperature drying is 90-150° C., and the target moisture content is 5-8wt%.

9. The anti-counterfeiting material obtained by the preparation method according to any one of claims 1 to 8, wherein the friction coefficient, texture and mechanical properties of different areas on the surface of the anti-counterfeiting material are different.

10. Use of the anti-counterfeiting material according to claim 9 in the field of anti-counterfeiting.

Citation Information

Patent Citations

  • Fluorosilicones and fluorine- and silicon-containing surface treatment agent

    CN101939347A

  • Anti-counterfeiting safety belt and the anti-counterfeiting paper on which the anti-counterfeiting safety belt is applied.

    CN102296486A

  • Manufacture method for non-woven fabric false-proof printing base material

    CN103722923A

  • Natural flower and grass anti-fake reduction-state Xuan paper and preparation method thereof

    CN107034718A

  • Anti-ultraviolet functional hair fiber surface treatment process

    CN117737994A